2018
DOI: 10.5559/di.27.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Budget Transparency of Local Governments: The Political Economy of City and Municipality Budgets in Croatia

Abstract: This paper investigates the budget transparency of Croatian local governments, i.e., the relationship between the open local budget index (OLBI) and a set of economic, political and socio--cultural variables. It uses a unique panel database of all 128 cities and 428 municipalities in 2015 and 2016. To examine the differences among the samples and years and to determine whether the different samples have different driving forces, a regression analysis based on a Poisson distribution is used. In the total (citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
10
0
4
Order By: Relevance
“…For the the citizen_wealth variable, the results are positive and significant only in the Croatian sample as previously proved in Ott et al, (2018) and . This indication of Croatian LGUs with a higher average income p.c.…”
Section: Results and Analysissupporting
confidence: 74%
See 3 more Smart Citations
“…For the the citizen_wealth variable, the results are positive and significant only in the Croatian sample as previously proved in Ott et al, (2018) and . This indication of Croatian LGUs with a higher average income p.c.…”
Section: Results and Analysissupporting
confidence: 74%
“…These results are consistent for all three samples and in all the models estimated. Several authors also found that population positively affects local governments' budget/fiscal transparency (De Araújo and Tejedo-Romero, 2016;del Sol, 2013;Guillamón et al, 2011;Styles and Tennyson, 2007;Ott et al, 2018;, Benčina et al, 2019. Explanations are usually given in two directions.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays we have a few studies dedicated to local budget transparency assessment with regard to institutional environment in the CEE countries: Ott et al (2006Ott et al ( , 2018, Andronova et al (2018), Sedmihradska (2015). Recent input to analyzing local fiscal transparency in Ukraine is presented in Demydenko and Nakonechna (2016), Slukhai et al (Слухай et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%